Nurses’ Attitudes Toward Death and Associations with Background Characteristics - Vognsen, Julie; Hernandez-Gantes, Victor M.; Chen, Yi-Hsin (British Journal of Healthcare and Medical Research, 2024)
In the United States, the majority of deaths occur in a medical facility. As such, the nurses’ attitudes toward death are crucial. Thus, this study examined nurses’ attitudes toward death and the impacts of demographic variables on their attitudes. The Death Attitude Profile-Revised (DAP-R) survey was used, including three subsets: Anxiety toward death (fear and avoidance), escape acceptance (death as a way to escape life’s troubles), and neutral acceptance (neither anxious nor too accepting). A demographic survey documented background characteristics, including gender, state of residence, year of experience, ethnicity, and area of nurse practice. There was a total of 168 participants, excluding missing data. Descriptive statistics and multiple regression analyses were conducted. This study found that nurses had low anxiety, moderate to high escape, and high neutrality to death. Year of experience and area of nurse practice (management versus extended care) showed statistically significant effects on the escape attitude. No overall predicting models showed statistically significant effects on nurses’ anxiety and neutrality attitudes toward death. More experienced nurses might have less anxiety, and Caucasian nurses might have less neutrality than other nurses. Further research is warranted.